2020
DOI: 10.3390/pharmaceutics12050458
|View full text |Cite
|
Sign up to set email alerts
|

Highly Elastic and Water Stable Zein Microfibers as a Potential Drug Delivery System for Wound Healing

Abstract: The development of biomaterials for wound healing applications requires providing a number of properties, such as antimicrobial action, facilitation of cell proliferation, biocompatibility and biodegradability. The aim of the present study was to investigate morphological and mechanical properties of zein-based microfibers, ultimately aimed at creating an environment suitable for wound healing. This was achieved through co-axial electrospinning of core–shell microfibers, with zein protein in the core and polye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 68 publications
(98 reference statements)
1
22
0
Order By: Relevance
“…Due to its high evaporation rate, it leads to needle clogging, formation of ribbon-shaped fibers and results in poor water stability of the fibers, which in turn leads to the loss of porous structure of the fiber mat upon contact with water [ 41 , 42 ]. This can be overcome either by cross-linking zein with UV light [ 71 ] or by co-axial electrospinning with ethanol [ 41 ] or polyethylene oxide (PEO) as a shell solution [ 54 ]. The behavior of zein in aqueous ethanol solution is described in more detail elsewhere [ 72 ].…”
Section: Electrospinning Of Plant-derived Proteins For Wound Healimentioning
confidence: 99%
See 2 more Smart Citations
“…Due to its high evaporation rate, it leads to needle clogging, formation of ribbon-shaped fibers and results in poor water stability of the fibers, which in turn leads to the loss of porous structure of the fiber mat upon contact with water [ 41 , 42 ]. This can be overcome either by cross-linking zein with UV light [ 71 ] or by co-axial electrospinning with ethanol [ 41 ] or polyethylene oxide (PEO) as a shell solution [ 54 ]. The behavior of zein in aqueous ethanol solution is described in more detail elsewhere [ 72 ].…”
Section: Electrospinning Of Plant-derived Proteins For Wound Healimentioning
confidence: 99%
“…There are various studies, which focus on electrospinning zein to produce antimicrobial wound dressings ( Table 1 ). Zein has been electrospun alone [ 45 , 50 , 51 , 52 , 53 ], together with synthetic polymers such as polycaprolactone (PCL) [ 47 , 48 ], PEO [ 54 ], PU [ 27 ] and PLA [ 55 ] as well as with natural polymers and substances including gum arabic [ 47 , 48 ], hyaluronic acid [ 46 ], cinnamaldehyde [ 26 ] and gum traganth [ 55 ]. Antimicrobial agents that have been incorporated into zein-based fibers include a wide range of antibiotics [ 26 , 45 , 46 , 49 , 51 , 54 , 55 ], antibacterial nanoparticles [ 27 , 50 , 52 ] as well as antimicrobial plant extracts [ 46 , 73 ].…”
Section: Electrospinning Of Plant-derived Proteins For Wound Healimentioning
confidence: 99%
See 1 more Smart Citation
“…They observed that increasing the polymer concentration and aging time can facilitate the formation of continuous fibers or ribbons. Akhmetova et al 31 reported a production of zein coaxial electrospinning of core‐shell microfibers, with zein in the core and PEO in the shell for wound healing applications. The authors concluded that the addition of PEO improves electrospun fiber formation and increases the elasticity of the microfiber mats.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated that the electrospinning technique has been widely employed in health care systems including drug delivery, diagnostics, theranostics, tissue engineering, and wound healing [ 19 , 20 , 21 , 22 , 23 , 24 ]. The multilayer electrospun membrane-based personalized reusable face mask has also been developed with photothermal application to disinfect the virus particles [ 25 ].…”
Section: Introductionmentioning
confidence: 99%